Surgical treatment of stenotic–occlusive affections of the lower extremity arteries in patients, suffering ischemic form of the diabetic foot syndrome - S. М. Didenko (Клінічна хірургія, 2018)
Objective. To compare the efficacy of different methods of surgical treatment for stenotic-occlusive affection of the lower extremities (LE) arteries in patients with ischemic form (ІF) of diabetic foot syndrome (DFS).